Genetic variability in a breeding population of eucalyptus urophylla s.T. Blake - Leite, S. M.M. [UNESP]; Bonine, C. A. [UNESP]; Mori, E. S.; Do Valle, C. F. [UNESP]; Marino, C. L. [UNESP] (My University, 2002)
Tree breeding programs have been under tremendous pressure to show results since the demand for the derived products has greatly increased. Molecular markers have been used in breeding programs in an attempt to evaluate the genetic bases of populations involved in breeding programs, identify hybrids and parental lines, etc. The aims of this study were to evaluate genetic variability of a base population of Eucalyptus urophylla using RAPD, to assess the genetic base of populations and to construct a molecular data bank. The base population consisted of 61 individuals of Flores and Timor provenance and a local commercial variety. Seventy polymorphic loci were analyzed. The mean genetic similarity was 0.3168 for the base population and the commercial variety showed the lowest similarity (0.2885). Crosses based on genetic distance were proposed.
Keywords: Breeding population; Crosses; Eucalyptus urophylla; Genetic similarity; Genetic variability; Molecular markers; RAPD